Oral health and quality of life in pregnant women at the Centro de Salud Cooperativa Universal during February-July 2016 - Tolentino Valencia, Raquel Elizabeth (2017)
Objective: To determine the relationship between oral health and quality of life of pregnant women at the Centro de Salud Cooperativa Universal. Materials and methods: A quantitative, observational, descriptive, cross-sectional, retrospective-prospective study of a population of 116 pregnant women during the three trimesters of pregnancy, from February to July 2016, who attended the dental outpatient department of the Centro de Salud Cooperativa Universal. Results: The most frequent maternal age ranged from 20 to 34 years old (65.1%), and the third trimester of pregnancy was the most common one (57%). Sixty-five point one percent (65.1%) of pregnant women had a fair quality of life, 20.9% had a good quality of life and 14% had a poor one. Eighty-seven point two percent (87.2%) of pregnant women had a fair level of oral hygiene with a prevalence of cavities of 11.2%. Conclusions: Oral health and quality of life of pregnant women showed a direct and moderate relationship, due to a fair level of oral hygiene and a high prevalence of dental caries. Both variables are closely linked, demonstrating their impact on pregnant women’s general health and quality of life.